TELAAH ASPEK BIOLOGI KEPITING BAKAU (Scylla spp) TERTANGKAP DI AREAL EKOSISTEM MANGROVE KABUPATEN PASANGKAYUPROVINSI SULAWESI BARAT - Tamsil, Andi; Ihsan, Ihsan; Hasnidar, Hasnidar; Asni, Andi; Ulat, Muhammad Ali (Politeknik Kelautan dan Perikanan Sorong, 2023)
The coastal area of Pasangkayu Regency, has the potential of mangrove crab resources, which have not been utilized optimally. This study aims to determine the species composition, and biological aspects of the mangrove crab Scylla spp caught in the Fold trap in the mangrove ecosystem area in Pasangkayu Regency, West Sulawesi Province, Indonesia. The research was carried out from March to June 2020. The materials used consisted of the Global Positioning System (GPS), Camera; and digital scales and rulers. Types of data collected include primary and secondary data. Primary data were collected from surveys and field observations, secondary data were collected from various related agencies. Data analysis includes species composition and biological aspects. The results of the identification of mangrove crabs found 2 types of mud crabs, Scylla serrata and Scylla olivacea, which were more dominant than Scylla olivacea. The results of the analysis of the biological aspect showed that the mangrove crab species were Scylla serrata in the allometric minor category and Scylla olivacea in the isometric category. The size distribution of long class frequencies, types of Scylla serrata and Scylla olivacea. The sex ratio of Sylla serrata is in the balanced category and Sylla olivacea is not balanced, the number of females is less than males. The rate of exploitation of the two types of mangrove crab Scylla serrata and Scylla olivacea is still rational and sustainable, the E value <0.5% or the highest E value 0.5% is still considered sustainable. The conversion rate of mangrove ecosystems for various purposes needs to be reduced so that the mangrove crab habitat area is maintained.